The Impact of COVID on Adolescent Mental Health, Self-Harm and Suicide: How Can Primary Care Provider Respond? A Position Paper of the European Academy of Pediatrics - Michaud, Pierre-André; Michaud, Laurent; Mazur, Artur; Hadjipanayis, Adamos; Kapp, Carole; Ambresin, Anne-Emmanuelle (Frontiers in Pediatrics, 2022)
Adolescents aged 10 to 19 live a period of their life marked by opportunities and vulnerabilities during which the issue of mental health is of prime importance. Since several decades, and especially since the start of the COVID pandemic, mental health problems and disorders among adolescents have increased around the world. Depression, self-harm and suicidal behaviour are common during this period of life, and paediatricians can play a pivotal role in identifying affected or vulnerable youngsters. This article describes risk factors for self-harm and suicidal behaviour and reviews how primary care paediatricians and health professionals can respond to such situations. It suggests concrete actions that can be taken to secure the life of at risk teenagers, and discusses how to organize the transfer to mental health professionals when needed.